Ultra-High-Throughput Multi-Core AES Encryption Hardware Architecture - Dong, Pham Khoi; Nguyen, Hung K; Hussin, Fawnizu Azmadi; Tran, Xuan Tu (VNU Journal of Science: Computer Science and Communication Engineering; Vol 37 No 2 (2021), 2021)
Security issues in high-speed data transfer between devices are always a big challenge. On the other hand, new data transfer standards such as IEEE P802.3bs 2017 stipulate the maximum data rate up to 400 Gbps. So, security encryptions need high throughput to meet data transfer rates and low latency to ensure the quality of services. In this paper, we propose a multi-core AES encryption hardware architecture to achieve ultra-high-throughput encryption. To reduce area cost and power consumption, these cores share the same KeyExpansion blocks. Fully parallel, outer round pipeline technique is also applied to the proposed architecture to achieve low latency encryption. The design has been modelled at RTL (Register-Transfer-Level) in VHDL and then synthesized with a CMOS 45nm technology using Synopsys Design Compiler. With 10-cores fully parallel and outer round pipeline, the implementation results show that our architecture achieves a throughput of 1 Tbps at the maximum operating frequency of 800 MHz . These results meet the speed requirements of future communication standards. In addition, our design also achieves a high power-efficiency of 2377 Gbps/W and area-efficiency of 833 Gbps/mm 2 , that is 2.6x and 4.5x higher than those of the other highest throughput of single-core AES, respectively.